Chemoprotective Horizons: Bioactive Molecules as Therapeutic Shields Against Cytotoxicity - Mary Martin, Taniya; Kishore Kumar, Meenakshi Sundaram (Asian Pacific Journal of Cancer Biology, 2025)
Chemotherapy remains a cornerstone in cancer management, but its lack of selectively between malignant and normal proliferating cells leads to widespread toxicities that significantly reduce patient quality of life and treatment adherence. Recent research has highlighted the promising role of naturally derived bioactive compounds in mitigating chemotherapy induced damage. These compounds, including polyphenols, flavonoids, terpenoids, and alkaloids, exhibit antioxidant, anti-inflammatory, anti-apoptotic, and organoprotective properties through diverse molecular pathways. Agents such as curcumin, resveratrol, quercetin, betanin, theaflavin and thymoquinone have demonstrated significant efficacy in reducing oxidative stress, modulating inflammatory cytokines, stabilizing mitochondrial function, and preserving normal tissue architecture in preclinical and early clinical studies. Importantly, many of these compounds selectively protect normal cells without reducing the cytotoxic effect of chemotherapeutic agents on tumor cells. Advances in formulation technologies, such as nanoencapsulation and combination strategies, further enhance their bioavailability and clinical applicability. This review discusses the mechanistic basis, experimental evidence, and translational potential of bioactive compounds as cytoprotective agents in chemotherapy, underscoring their future role in integrative cancer care.